Impact of Advertising on Consumer Purchase Decision in Sudan - Ismail Ibrahim , Mujahid Adam (International Journal of Management Excellence (ISSN: 2292-1648), 2020)
Advertisements are a tool of communication used in the marketing and promotion of a product or service by the brand. It promotes an integrated marketing communication which emotionally motivates the consumers to make purchases. The advertisement has a strong linkage with the proliferation of the media and the entertainment industry. This research aimed to investigate the impact of advertisements on consumer purchase decisions. The research methodology adopted a primary research design with a quantitative and qualitative approach. Five hundred questionnaires were distributed and 466 questionnaires were collected and included in the study. As per the statistical analysis, a strong positive correlation has been found between advertisement and consumers purchasing decisions. The investigation of this study indicate that consumers consider TV as the most effective tool for the promotion of certain brand products or services. Also, study find that, Purchase decisions were also affected by the seller’s way of showing the product or the method of advertisement. Therefore, there are chances for those interested in the marketing domain to benefit from the findings of this research and may use them to analyse what aspects of advertisements change the buying behaviour and purchasing decisions of consumers.